CIPP Model Evaluation: Project on Strengthening the Profile of Pancasila Students (P5) in Palabuhanratu Area High Schools - Irfan Giovani Ribisi; Griet Helena Laihad; Eka Suhardi (STAI Hubbulwathan Duri, 2024)
This study evaluates the effectiveness of the Pancasila Student Profile Strengthening Program (P5) in achieving the objectives of the Merdeka Curriculum in the Pelabuhanratu Region, focusing on character development and student potential. A misalignment between the curriculum goals and schools’ vision emphasizing academic achievement was identified as a critical issue. Using a qualitative descriptive approach and the CIPP (Context, Input, Process, Product) evaluation model, data were collected through semi-structured interviews, document analysis, and field observations. Informants included school principals, deputy principals, teachers, students, parents, and school supervisors. Data were scored on a scale of 1–5 to assess various program components. The context component scored well (4.0), indicating alignment with policy, goals, and objectives. Input evaluation revealed strengths in resources (4.1) but weaknesses in budgeting (1.8), cooperation (1.7), and organizational structure (2.5). Process evaluation highlighted adequate planning (3.3) and reporting (3.4) but identified deficiencies in implementation (2.9), supervision (2.1), and follow-up (2.2). Product evaluation rated outcomes as good (3.2), with a high impact score (3.9), though benefits require improvement (2.7). Among 150 students, high achievements were observed in Creativity (85%) and Faith (77%) but lower in Critical Thinking (51%) and Independence (61%). The findings highlight critical gaps in resource allocation, supervision, and program benefits. Recommendations are provided to address these challenges and enhance program alignment with the Merdeka Curriculum. This study provides insights into P5 implementation challenges and offers pathways for program improvement to better align with curriculum goals.